WHAT SHOULD BE THE FORM OF PUBLIC PARTICIPATION IN THE LAWMAKING PROCESS? AN ANALYSIS OF SOUTH AFRICAN CASES - Moses Retselisitsoe Phooko (Obiter, 2014)
South Africa’s new constitutional democracy places a duty on various legislators to facilitate public participation in the law-making process as mandated by the principles of participatory democracy provided for in the Constitution of South Africa, 1996. This has resulted in a series of court cases wherein the electorate, inter alia, challenged the legislation on the basis that the results did not reflect the views of the people. The courts’ earlier jurisprudence seemed to be placing more emphasis on participatory democracy as opposed to representative democracy. However, recent court decisions indicate a shift towards representative democracy. The central question presented in this paper is whether the consideration of the views of the public by the provincial and national legislatures is merely a matter of procedure, or that those views are indeed considered in the law-making process. In an attempt to answer this question, the paper will evaluate and critique some of the Constitutional Court and the Supreme Court of Appeal decisions on public involvement in either the legislative or law-making process. The argument presented in this discourse is that, if the public’s wishes are considered by the legislature, then the outcome would be influenced by the people’s demands. An otherwise negative outcome shows that public participation in the law-making process is a procedural matter and has no substantive value.